2020
DOI: 10.3390/su13010243
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Virtual Reality Technology in Safety Training Solution for Construction Site of Urban Cities

Abstract: The lack of experiential training has become the primary cause of incidents that could have been easily avoided in construction areas, and the implementation of experimental training is crucial in minimizing incidents at construction sites. The limitation on the available training tools has made it impossible to build up a real test site or reproduce the constructing scenarios. This research aims to develop an immersive and interactive multiplayer-based training platform that incorporates virtual reality (VR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 27 publications
0
33
0
3
Order By: Relevance
“…Zhao et al [43,44] and Fang et al [45] focused their studies on training workers to avoid having hazardous behaviours, for example when they use a crane. Finally, in the same line, Xu et al [46] and Joshi et al [47] conducted objective and subjective user evaluations on VR training for safety, which confirmed the benefits of this technology for construction workers. Nonetheless, the use of VR has also been studied for other purposes than training, and notably as an environment that can allow safety managers to detect design or construction planning defects that would engender hazardous zones in the future worksite [48][49][50][51].…”
Section: Introductionmentioning
confidence: 74%
“…Zhao et al [43,44] and Fang et al [45] focused their studies on training workers to avoid having hazardous behaviours, for example when they use a crane. Finally, in the same line, Xu et al [46] and Joshi et al [47] conducted objective and subjective user evaluations on VR training for safety, which confirmed the benefits of this technology for construction workers. Nonetheless, the use of VR has also been studied for other purposes than training, and notably as an environment that can allow safety managers to detect design or construction planning defects that would engender hazardous zones in the future worksite [48][49][50][51].…”
Section: Introductionmentioning
confidence: 74%
“…e main purpose of VR technology is to simulate and restore the real environment. It virtualizes some things in the real world in the form of symbols to build a virtual world beyond the limitations of the real environment [12]. Humans perceive the environment in the real world through vision, touch, and hearing, and VR technology simulates these perception methods to a great extent.…”
Section: Research Theories and Methodsmentioning
confidence: 99%
“…To bridge these gaps, several researchers adapted and used VR-based training methods for risk assessment training such as the abovementioned list of risk assessment steps in various high-risk engineering industries such as in construction (Ahn et al, 2020;Albert et al, 2014;Han et al, 2021;Joshi et al, 2021;Kazar & Comu, 2021;Lin et al, 2011Lin et al, , 2018Pedro et al, 2020;Perlman et al, 2014;Pham et al, 2019;Xu & Zheng, 2021), chemical process/laboratory (Kwegyir-Afful et al, 2021;Nazir et al, 2015;Nicoletti & Padovano, 2019;Stransky et al, 2021;Tawadrous et al, 2017), manufacturing and assembly (Diego-Mas et al, 2020), and mining (Isleyen & Duzgun, 2019), as these technologies can recreate a realistic but safe 3D environment of some hazardous workplace scenarios where the trainees can improve their risk assessment skills through the learning-by-doing approach (Fig. 3).…”
Section: What Topics Have Researchers Investigated For Vr-based Healt...mentioning
confidence: 99%
“…Among the 16 papers, the results of a statistical test (e.g., t-test, ANOVA, etc.) of the 13 studies showed that the VRbased training provides a greater degree of reaction level compared to the traditional setting (Ahn et al, 2020;Beh et al, 2021;Diego-Mas et al, 2020;Guo et al, 2012;Joshi et al, 2021;Leder et al, 2019;Li et al, 2012;Makransky et al, 2019;Nykänen et al, 2020;Pham et al, 2019;Poyade et al, 2021;Sacks et al, 2013;Xu & Zheng, 2021). For instance, Leder et al (2019), stated that compared to the traditional training method (PowerPoint presentation), there was a better degree of immersion and presence in the semi-immersive VR (CAVE) condition.…”
Section: Does Vr-based Health and Safety Training In Various High-ris...mentioning
confidence: 99%